1995
DOI: 10.1007/bf02790134
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationship of flavonoids with superoxide scavenging activity

Abstract: The superoxide scavenging activities of 12 flavonoids were measured. The superoxide anions were generated by a hypoxanthine-xanthine oxidase system and measured by the nitrite method. The results showed that the scavenging ability enhanced with an increasing number of hydroxyl groups in ring B. Substitution at C3 position with a hydroxyl group increased the activity. Compared to a methoxyl group or a glycoside in this position, a free hydroxyl group showed the highest activity. A saturated C2-C3 bond showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
98
0
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 6 publications
7
98
0
4
Order By: Relevance
“…The general structure of major flavonols detected in Tilia platyphyllos leaves is shown (Hu et al 1995) or to a synthetic free radical (2,2'-azinobis-(3-ethylbenzothiazoline-6-27 sulfonic acid, ABTS) used in assessing total antioxidant capacities (Heim et al 2002). found that myricetin which contains three of these hydroxyl groups but was not included in 31 the above study had the highest reactivity to 1 O 2 .…”
mentioning
confidence: 82%
“…The general structure of major flavonols detected in Tilia platyphyllos leaves is shown (Hu et al 1995) or to a synthetic free radical (2,2'-azinobis-(3-ethylbenzothiazoline-6-27 sulfonic acid, ABTS) used in assessing total antioxidant capacities (Heim et al 2002). found that myricetin which contains three of these hydroxyl groups but was not included in 31 the above study had the highest reactivity to 1 O 2 .…”
mentioning
confidence: 82%
“…Epidemiological studies have shown that there is an inverse association between the intake of flavonols and flavones and the risk of coronary heart disease [20][21][22], stroke [23] and lung cancer [24]. The position and the degree of hydroxylation have been demonstrated to be the most important for their biochemical and pharmacological actions [25,26]. Wang et al [11] examined the antioxidant and antiinflammatory activities of selected flavonols, including kaempferol, quercetin and myricetin.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1. Current interest in the compounds of flavonoid group, including 1, is explained by their varied biological activity, with antioxidant, antiradical, hepatoprotective, anti-inflammatory and other interesting properties [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%